The start of the first chapter of "Das Kommunistisch Manifest", in which Marx' portrait is created through variation in the thickness of the letters. See also BG E11/780 and BG E12/251; slightly different versions (1977)
The start of the first chapter of "Das Kommunistisch Manifest", in which Marx' portrait is created through variation in the thickness of the letters. See also BG E11/780 and BG E12/251; slightly different versions.